Peranan Komunikasi Organisasi Dalam Meningkatkan Kinerja Pegawai Negeri Sipil Di Sekretariat Daerah Kabupaten Sorong - Lossu, Gladis; Liando, Daud (JURNAL ILMIAH SOCIETY, 2016)
Communication holds a very important role in organization. The aim is to build the cooperation between humans who involve in organization and possess the effect in the process of achieving the organization goal. The aim of this research are to find and analyze the role of organizational communication in increasing the performance of the civil Servant in secretariat office of Sorong Regency. The method used in this research was qualitative, data were collected by observation participation, structured interview, and documentation. The result showed that the role of organization communication in increasing the performance of the civil Servant in secretariat office of Sorong Regency did not work effectively and efficiently. The role of leadership in organization still less, it can be seen from the minimum number of direct briefing from the leader toward the effective working mechanism. The role of the organization environment toward human resources in secretariat office of Sorong Regency related to position assignment in every post did not suit to the civil servant educational background. The civil servant performed uncaring service to the society. The motivation role in achieving the organization role is insufficient and the ignorance of the civil servant toward the job description. Keywords: communication role, Civil servant performance